Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0326
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiratory Complex Biogenesis: Communication, Gene Expression and Assembly

Abstract: The sections in this article areIntroductionBiogenesis of Prosthetic Groups Essential for RespirationMitochondrial Respiratory Complexes AssemblyGene Expression for the Biogenesis of Mitochondrial Respiratory ComplexesMitochondria–Nucleus Cross TalkConcluding RemarksAcknowledgements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…Careful examination of the A. thaliana genome revealed that two genes encode similar yeast COX17 homologs, respectively, AtCOX17-1 and AtCOX17-2 which functions remain to be elucidated. However, since COX17 is a highly conserved protein, one can assume that the six conserved cysteine residues of Cox17 that participate in the ligation of Cu(I) in both yeast and mammalia perform a similar function in plants to allow Cu transfer from cytosol to the mitochondrial inter-membrane space ( Palumaa et al, 2004 ; Giegé, 2007 ).…”
Section: Copper Trafficking In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful examination of the A. thaliana genome revealed that two genes encode similar yeast COX17 homologs, respectively, AtCOX17-1 and AtCOX17-2 which functions remain to be elucidated. However, since COX17 is a highly conserved protein, one can assume that the six conserved cysteine residues of Cox17 that participate in the ligation of Cu(I) in both yeast and mammalia perform a similar function in plants to allow Cu transfer from cytosol to the mitochondrial inter-membrane space ( Palumaa et al, 2004 ; Giegé, 2007 ).…”
Section: Copper Trafficking In Plantsmentioning
confidence: 99%
“…In particular, HCC1 loss of function was shown to disrupt COX activities whereas HCC2 may rather indirectly act in redox regulation ( Attallah et al, 2011 ; Steinebrunner et al, 2014 ). Finally, the presence of a COX11 homolog in the Arabidopsis genome, being potentially able to bind Cu(I) and to participate in the formation of the Cu B metal center of the COX, suggests a role of this later at some terminal stage of cytochrome c oxidase synthesis, notably in inserting Cu into subunit I ( Horng et al, 2004 ; Giegé, 2007 ).…”
Section: Copper Trafficking In Plantsmentioning
confidence: 99%
“…Both groups concluded that Viscum mitochondrial genes are very deviating from genes of even closely related taxa, and that they lack all genes of complex I (NAD-ubiquinone oxidoreductase complex). The NADH-ubiquinone oxidoreductase complex (mitochondrial complex I) is the largest in the plant mitogenome (in A. thaliana it is comprised of 48 subunits, 9 of which are encoded in its mitogenome (Giegé 2007)). It is there, where the initial electron transfer occurs that starts the oxidative phosphorylation pathway (Remacle et al 2008).…”
Section: Introductionmentioning
confidence: 99%